Interpretation of 2D resistivity with engineering characterization of subsurface exploration in Nusajaya Johor, Malaysia - Mohd Akip Tan, S. N.; Md Dan, M. F.; Edy Tonnizam, M.; Saad, R.; Madun, Aziman; Hazreek, Z. A. M. (IOP Publishing, 2018)
2-D resistivity technique and pole-dipole array with spacing of 2 m electrode and total spacing of 80 m were adopted to map and characterize the shallow subsurface in a sedimentary area at Nusajaya, Johor. Geological field mapping and laboratory testing were conducted to determine weathering grades.Res2Dinv software was used to generate the inversion model resistivity. The result shows sandstone contains iron mineral (30-1000ohm-m) and weathered sandstone (500-1000 ohm-m). The lowest layer represents sandstone and siltstone with the highest range from 1500 through 5000 ohm-m. The weathering grade IV and V of sandstone in the actual profile indicates the range from 30 to 1000 ohm-m, whereas grade II and III in ground mass matched the higest range. Overall, the increase of weathering grade influenced both the physical properties and strength of rocks.